Rattus xanthurus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
693. North-eastern Xanthurus Rat Rattus xanthurus French: Rat & queue jaune / German: Nordostliche Gelbschwanzratte / Spanish: Rata de cola dorada nororiental Other common names: Yellow-tailed Forest Rat, Yellow-tailed Rat Taxonomy. Mus xanthura [sic] Gray, 1867, “North Celebes [= north Sulawesi, Indonesia]; Tondano... 3600 feet [= 1069 m].” Rattus xanthurusis in the R. xanthurus species group along with R. marmosurus, R. salocco, R. bontanus, and R. pelurus, although taxo-nomic affinities of this group are not well known; the group is probably sister to the Recent New Guinea and Australian clade (leucopus / fuscipes and New Guinea species groups). Rattus xanthurus might represent multiple species, and the entire R. xanthurus species group is currently under revision. Distribution. NE part of the N peninsula of Sulawesi. Descriptive notes. Head—body 235-260 mm, tail 293-330 mm, hindfoot 45-48 mm. No specific data are available for weight. The North-eastern Xanthurus Rat is large, with harsh long pelage, ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 841, DOI: 10.5281/zenodo.6887260 ...